2016
DOI: 10.1080/21645515.2016.1219824
|View full text |Cite
|
Sign up to set email alerts
|

How do parents and pediatricians arrive at the decision to immunize their children in the private sector? Insights from a qualitative study on rotavirus vaccination across select Indian cities

Abstract: Key debates on improving vaccination coverage tend to focus on factors that affect uptake in the public health system while ignoring the private sector that plays an important role in providing health services in any low or middle-income country setting. Using in-depth interviews, we explored factors that influenced the decision of parents as well as pediatricians working in the private sector across 8 Indian cities on whether their children should be vaccinated with a particular vaccine Pediatricians and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Knowledgeable of the disease and the vaccine will influence the acceptance of the vaccine. As with previous studies, our study found that primary HCPs have an essential role in parental vaccine decisions [21], [29].…”
Section: Discussionsupporting
confidence: 89%
“…Knowledgeable of the disease and the vaccine will influence the acceptance of the vaccine. As with previous studies, our study found that primary HCPs have an essential role in parental vaccine decisions [21], [29].…”
Section: Discussionsupporting
confidence: 89%
“…In India, a survey revealed that factors such as the relationship with the pediatrician and vaccination-related decisions taken by people in the immediate social network were important drivers for decisions about vaccination against RV. 46 Our survey showed that other channels including the government/department of health/ministry of health websites, family and friends, disease/vaccination awareness posters in doctor's offices, hospitals, or pharmacies, pharmacists and vaccination information leaflets were also influential. Social media could also play a role, especially in Indonesia and Thailand, where approximately a quarter of participants rank it in their top five most likely channels to refer to (a mean of 24% in Indonesia and 27% in Thailand).…”
Section: Discussionmentioning
confidence: 82%
“…While immunization is a priority program for the public health system, due to large number of people accessing the private health sector, health care providers from private sector also play important role in overall success of immunisation. 31 However, awareness regarding need for rotavirus vaccination and vaccine schedule is also important for frontline health workers in public health system who are responsible for vaccination coverage at grass root level. 32 Thus, there is need for effective communication methods regarding rotavirus vaccination amongst all cadres of health care providers and frontline workers.…”
Section: Discussionmentioning
confidence: 99%